Систем за македонски знаковен jазик наменет за лицата со оштетен слух - Јоксимоски, Бобан (ФИНКИ, УКИМ, Скопје, 2020)
There are a huge number of languages in the world for communication. They are usually divided into a large number of categories and types, most often by genealogical classification, as well as the type of communication (verbal and non-verbal). It is estimated that over 360 million people worldwide are affected by partial of full hearing loss and consequently problems with standard verbal communication through usage of phonetic units (sounds). The Deaf population faces challenges in integrating into society and belongs to a different subculture and language group, further widening the gap among them and the general population. As a basic way to reduce the gap between people with significant hearing loss and people that have normal hearing is to overcome the "language barrier that is, to find appropriately expressive mode of communication. Sign languages represent visual languages that use movement of hands, body and facial expressions to express the appropriate message. This thesis explores the use of sign languages as a basic modality to carry out communication. At the same time a special aspect is given to Macedonian sign language, its use and analysis of the requirements for visualization system for the Macedonian Sign Language. Based on this, a system for sign language visualization is proposed, with a particular aspect of visualization of the Macedonian sign language. The system consists from several modules: visualization, digital vocabulary, translation system for text into a notation system suitable for the Macedonian sign language. Additionally, the thesis discusses options for the creation and acquisition of sign language by speakers of the Macedonian sign language.
Докторска дисертација одбранета во 2020 година на Факултетот за информатички науки и компјутерско инженерство во Скопје, под менторство на проф. д–р Драган Михаjлов.